Distributed stochastic security constrained unit commitment for coordinated operation of transmission and distribution system - Aamir Nawaz; Hongtao Wang (CSEE Journal of Power and Energy Systems, 2021)
With the high penetration of renewable energies in modern power systems, deterministic coordination algorithms are facing two major problems: one is degradation in accuracy if fewer scenarios are utilized for uncertainty evaluation while second is the high computational time if a high number of scenarios are considered for better accuracy. In both cases, the efficiency of the algorithm is degraded. To solve these problems in coupled transmission system and distribution systems (TSDS), probabilistic coordination algorithms are adopted to solve with less effort. In this paper, a TSDS probabilistic coordination model is proposed to solve the coordinated security-constrained unit commitment problem. A mean and standard deviation matching based probabilistic analytical target cascading algorithm has been utilized for evaluation of TSDS coordination problem. Instead of solving each scenario as a separate problem, the proposed algorithm considers a single coordination problem with probabilistic characteristics as shared variables and hence, achieves fast convergence. Different case studies are performed to prove the efficacy of the proposed algorithm. Results verify that the proposed algorithm reduces computational time and resources for large-scale systems.